A lithium-rich manganese-based positive electrode material and its preparation method and application
By increasing the incorporation amount of lanthanum element and optimizing the preparation steps, the electrochemical performance and cyclic stability of lithium-rich manganese-based cathode materials are solved, and the improvement of rate performance and cyclic performance and voltage attenuation are achieved.
Patent Information
- Application Number
- CN202411426587.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-14
AI Technical Summary
Lithium-rich manganese-based cathode materials have problems such as low initial Coulomb efficiency, poor cycle rate performance and serious voltage attenuation, which affect their application.
By increasing the incorporation amount of lanthanum, using the large ion radius of La3+ and the strong La-O bond energy, the material structure is supported and the diffusion rate of lithium ions is accelerated, and the generation of oxygen vacancies is slowed down through the strong La-O bond. Blocks the migration path of transition metal ions.
The rate performance and cycling performance of lithium-rich manganese-based cathode material are significantly improved, and the voltage attenuation during long cycles is suppressed.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a lithium-rich manganese-based positive electrode material and a preparation method and application thereof. Background Art
[0002] Lithium-rich manganese-based materials have the characteristics of high capacity and high operating voltage, which can meet the high energy density requirements of power batteries and are the research hotspot of the next generation of lithium-ion battery positive electrode materials. However, the inherent defects of lithium-rich manganese-based materials, such as low initial coulombic efficiency, poor cycle rate performance and severe voltage decay, have affected the application of lithium-rich manganese-based materials.
[0003] In response to the above problems, some studies have improved the electrochemical performance of lithium-rich manganese-based materials by reducing the particle size of the material to shorten the lithium ion transmission path, or by increasing crystal defects through element doping to improve the overall performance of lithium-rich manganese-based materials, and by improving the electronic conductivity and lithium ion diffusion and migration rate of lithium iron phosphate through carbon coating. For example, the document "Preparation and Performance of Lithium-Rich Manganese-Based Positive Electrode Materials Modified by Lanthanum Elements" provides lithium-rich manganese-based positive electrode materials, which are prepared by coprecipitation and studied by lanthanum doping. By pinning a trace amount of lanthanum ions in the octahedral center of the transition metal layer, the unit cell parameters of the material are expanded, the migration rate of lithium ions is improved, and the cycle stability and voltage stability of lithium-rich manganese-based positive electrode materials are enhanced. However, the preparation process is complicated, and the raw materials used are expensive, which is not suitable for mass production. The document "The Effect of Lanthanum Doping on the Electrochemical Performance of Lithium-Rich Manganese-Based Cathode Materials" discloses a preparation method using sol-gel combined with high-temperature solid phase. In this method, citric acid and metal ions are weighed in a molar ratio of 1:1, and the two are poured into an appropriate amount of deionized water respectively, and mixed after being completely dissolved. During this process, a stirring magnet is used to stir continuously, and the mixed solution is stirred for a period of time and placed in an 80°C water bath to stir and evaporate the solvent. After the solvent is completely evaporated to form a transparent colloid, it is placed in a drying oven and dried before segmented sintering. However, the sol-gel method cannot stably synthesize lithium-rich manganese-based cathode materials with uniform particle radius, that is, the synthesis process is not stable. Summary of the invention
[0004] In view of this, the present invention provides a lithium-rich manganese-based positive electrode material and a preparation method and application thereof. The rate performance and cycle performance of a battery made from the lithium-rich manganese-based positive electrode material are significantly improved, and the voltage attenuation during a long cycle is also effectively suppressed.
[0005] In order to solve the above technical problems, the first aspect of the present invention provides a lithium-rich manganese-based positive electrode material, whose chemical formula is Li 1.5 Mn a Ni b Co c La dO3, wherein 0.3≤a<0.7, 0.3≤b<0.7, 0.3≤c<0.7, 0.3<d≤0.5 and 1<a+b+c+d≤2.
[0006] The present invention increases the amount of lanthanum added into the lithium-rich manganese-based positive electrode material, and utilizes La 3+ The large ionic radius and strong La-O bond energy enable the lanthanum ions to play a supporting role to support the material structure. At the same time, vacancies are generated around the lanthanum atoms inside the crystal, which accelerates the diffusion rate of lithium ions inside the material and is beneficial to the deintercalation kinetics of lithium ions. The lithium-rich manganese-based positive electrode material provided by the present invention not only does not cause the electrochemical performance of the lithium-rich manganese-based positive electrode material to decrease due to the increase in the lithium ion transmission path, but on the contrary, the migration rate of lithium ions is increased due to the expansion of the unit cell parameters of the material. Moreover, the introduction of more lanthanum elements can also slow down the generation of oxygen vacancies through stronger La-O bonds, blocking the migration path of transition metal ions, thereby enhancing the cycle stability and voltage stability of lithium-ion batteries prepared from lithium-rich manganese-based positive electrode materials.
[0007] In combination with the first aspect, the chemical formula of the lithium-rich manganese-based positive electrode material is Li 1.5 Mn 0.5 Ni 0.5 Co 0.5 La 0.5 O3.
[0008] A second aspect of the present invention provides a method for preparing the above-mentioned lithium-rich manganese-based positive electrode material, the steps comprising:
[0009] Add an appropriate amount of ammonia water into a reaction container, and dropwise add aqueous solutions of a manganese source, a nickel source, a cobalt source, and a lanthanum source, respectively, while stirring to obtain a first dispersion;
[0010] Adding a lithium hydroxide solution dropwise to the first dispersion, maintaining the pH of the system at 9-11, stirring to react, and performing solid-liquid separation, drying, and grinding to obtain a solid phase precursor;
[0011] Mixing the solid phase precursor with lithium hydroxide, and sintering at 700-800° C. under nitrogen protection to obtain the lithium-rich manganese-based positive electrode material;
[0012] The molar ratios of the manganese source, the nickel source, the cobalt source, the lanthanum source and the lithium hydroxide are 1-4:1-2:1-1.8:1-1.5:1-5 respectively.
[0013] In view of the problem of unstable process in the current preparation method of lithium-rich manganese-based positive electrode materials, the present invention provides a method for preparing lithium-rich manganese-based positive electrode materials, by adding a lithium source dropwise into an ammonia solution of transition metals and rare metals to react and produce a precipitate; the obtained solid-phase precursor is sintered with lithium hydroxide in nitrogen to successfully obtain a lithium-rich manganese-based positive electrode material with uniform particle size, thereby solving the problem of unstable synthesis process in the sol-gel preparation method.
[0014] In combination with the second aspect, the manganese source is selected from manganese oxalate, manganese acetate or manganese nitrate; the nickel source is selected from nickel oxalate, nickel acetate or nickel nitrate; the cobalt source is selected from cobalt oxalate, cobalt acetate or cobalt nitrate; the lanthanum source is selected from lanthanum oxalate, lanthanum acetate or lanthanum nitrate.
[0015] Preferably, the manganese source is manganese oxalate, the nickel source is nickel oxalate, and the cobalt source is cobalt oxalate.
[0016] In combination with the second aspect, the concentration of the aqueous solution of the manganese source, nickel source, cobalt source and lanthanum source is 4-6 mol / L, preferably 5 mol / L. The use of transition metal sources in this concentration range can make the prepared lithium-rich manganese-based positive electrode material have an ideal element distribution, which provides a guarantee for the subsequent preparation of lithium-ion batteries with excellent comprehensive performance.
[0017] In combination with the second aspect, the concentration of the lithium hydroxide solution is 4-6 mol / L, preferably 5 mol / L.
[0018] In combination with the second aspect, the mixing of the solid phase precursor with lithium hydroxide is specifically: mixing the solid phase precursor with lithium hydroxide, the mass of the lithium hydroxide being 103% to 105% of the total mass of the manganese source, the nickel source, the cobalt source and the lanthanum source.
[0019] In combination with the second aspect, the concentration of the ammonia water is 1-10 mol / L, preferably 2 mol / L.
[0020] In combination with the second aspect, the reaction time is 1 to 10 hours; the sintering time is 7 to 9 hours.
[0021] In combination with the second aspect, the drying is microwave drying, and the microwave power is 1600~3000W / m 2 The drying time is 1~3h, and the temperature is controlled at 50~60℃.
[0022] A third aspect of the present invention provides a positive electrode plate, wherein the positive electrode plate comprises a lithium-rich manganese-based positive electrode material prepared according to the above preparation method.
[0023] A fourth aspect of the present invention provides a lithium-ion battery, comprising the above-mentioned positive electrode plate.
[0024] Beneficial effects obtained by the present invention: By controlling the amount of lanthanum doping element added and improving the preparation steps, the present invention obtains a lithium-rich manganese-based positive electrode material that improves the rate performance and cycle performance of the lithium-ion battery, and also effectively suppresses the voltage decay of the lithium-ion battery during a long cycle. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0026] In traditional lithium-rich manganese-based cathode materials, the release of lithium ions and the migration of transition metals easily cause the material to transform from a layered structure to a spinel structure, which seriously hinders ion diffusion and causes a significant attenuation of battery voltage and capacity during the cycle. If the amount of lanthanum added is increased to the same or even higher than that of transition metal elements, the electrochemical performance of the resulting cathode material will be significantly improved, and the corresponding cycle stability and voltage stability of lithium-ion batteries will also be improved accordingly.
[0027] Example 1
[0028] This embodiment provides a lithium-rich manganese-based positive electrode material, whose chemical formula is Li 1.5 Mn 0.5 Ni 0.5 Co 0.5 La 0.5 O3, the specific preparation steps include:
[0029] Add 200mL of ammonia water (concentration of 1mol / L) to the reaction container, measure 100mL of each of manganese oxalate solution, nickel oxalate solution, cobalt oxalate solution and lanthanum oxalate solution with a concentration of 5mol / L, and add them dropwise to the ammonia water while stirring to obtain the first dispersion. While stirring, continue to drop 300mL of lithium hydroxide solution with a concentration of 5mol / L into the first dispersion, and adjust and maintain the pH of the system to 9~11 with an acidic or alkaline solution, and react for 4h. After the reaction is completed, filter and collect the filter cake, microwave dry it at 55℃, grind it, and obtain a solid phase precursor. The solid phase precursor is mixed with lithium hydroxide with a mass of 105% of the total mass of manganese oxalate, nickel oxalate, cobalt oxalate and lanthanum oxalate, and sintered at 750℃ for 8h under nitrogen protection to obtain a lithium-rich manganese-based positive electrode material.
[0030] Example 2
[0031] This embodiment provides a lithium-rich manganese-based positive electrode material, whose chemical formula is Li 1.5 Mn 0.55 Ni 0.48 Co0.62 La 0.4 O3, the specific preparation steps include:
[0032] Add 180mL of ammonia water (concentration of 5mol / L) to the reaction container, measure 137.5mL of 4mol / L manganese acetate solution, 120mL of 4mol / L nickel acetate solution, 155mL of 4mol / L cobalt acetate solution and 66.7mL of 6mol / L lanthanum acetate solution, respectively, and add them dropwise into the ammonia water while stirring to obtain the first dispersion. While stirring, continue to drop 250mL of 6mol / L lithium hydroxide solution into the first dispersion, and adjust and maintain the pH of the system to 9-11 with an acidic or alkaline solution, and react for 10h. After the reaction is completed, filter and collect the filter cake, microwave dry it at 50℃, and grind it to obtain a solid phase precursor. The solid phase precursor is mixed with lithium hydroxide whose mass is 103% of the total mass of manganese acetate, nickel acetate, cobalt acetate and lanthanum acetate, and sintered at 700℃ for 9h under nitrogen protection to obtain a lithium-rich manganese-based positive electrode material.
[0033] Example 3
[0034] This embodiment provides a lithium-rich manganese-based positive electrode material, whose chemical formula is Li 1.5 Mn 0.5 Ni 0.56 Co 0.5 La 0.46 O3, the specific preparation steps include:
[0035] Add 200mL of ammonia water (concentration of 10mol / L) to the reaction container, measure 125mL of 4mol / L manganese nitrate solution, 140mL of 4mol / L nickel nitrate solution, 100mL of 5mol / L cobalt nitrate solution and 115mL of 4mol / L lanthanum nitrate solution, respectively, and add them dropwise into the ammonia water while stirring to obtain the first dispersion. While stirring, continue to drop 375mL of 4mol / L lithium hydroxide solution into the first dispersion, and adjust and maintain the pH of the system to 9-11 with an acidic or alkaline solution, and react for 1h. After the reaction is completed, filter and collect the filter cake, microwave dry it at 60℃, and grind it to obtain a solid phase precursor. The solid phase precursor is mixed with lithium hydroxide whose mass is 104% of the total mass of manganese nitrate, nickel nitrate, cobalt nitrate and lanthanum nitrate, and sintered at 800℃ for 7h under nitrogen protection to obtain a lithium-rich manganese-based positive electrode material.
[0036] Comparative Example 1
[0037] This comparative example provides a lithium-rich manganese-based positive electrode material, the chemical formula of which is Li 1.5 Mn 0.7 Ni 0.7 Co0.7 La 0.1 O3, the specific preparation steps include:
[0038] Add 200mL of ammonia water (concentration of 2mol / L) to the reaction container, measure 140mL of each of 5mol / L manganese oxalate solution, nickel oxalate solution and cobalt oxalate solution, and 50mL of 2mol / L lanthanum oxalate solution, respectively, and add them dropwise into the ammonia water while stirring to obtain the first dispersion. While stirring, continue to drop 300mL of 5mol / L lithium hydroxide solution into the first dispersion, and adjust and maintain the pH of the system to 9-11 with an acidic or alkaline solution, and react for 4h. After the reaction is completed, filter and collect the filter cake, microwave dry it at 55℃, grind it, and obtain a solid phase precursor. The solid phase precursor is mixed with lithium hydroxide with a mass of 105% of the total mass of manganese oxalate, nickel oxalate, cobalt oxalate and lanthanum oxalate, and sintered at 750℃ for 8h under nitrogen protection to obtain a lithium-rich manganese-based positive electrode material.
[0039] Comparative Example 2
[0040] This comparative example provides a lithium-rich manganese-based positive electrode material, the chemical formula of which is Li 1.5 Mn 0.4 Ni 0.4 Co 0.4 La 0.7 O3, the specific preparation steps include:
[0041] Add 200mL of ammonia water (concentration of 4mol / L) to the reaction container, measure 80mL of each of manganese oxalate solution, nickel oxalate solution and cobalt oxalate solution with a concentration of 5mol / L and mix them with ammonia water, and adjust and maintain the pH of the system at 9-11 with an acidic or alkaline solution to obtain a first dispersion. While stirring, add the first dispersion dropwise to 140mL of lanthanum oxide suspension with a concentration of 5mol / L, and then add 300mL of lithium hydroxide solution with a concentration of 5mol / L to it to cause a precipitation reaction for 4h. After the reaction is completed, filter and collect the filter cake, microwave dry it at 55℃, grind it, and obtain a solid phase precursor. The solid phase precursor is mixed with lithium hydroxide with a mass of 105% of the total mass of manganese oxalate, nickel oxalate, cobalt oxalate and lanthanum oxalate, and sintered at 750℃ for 8h under nitrogen protection to obtain a lithium-rich manganese-based positive electrode material.
[0042] Comparative Example 3
[0043] This comparative example provides a lithium-rich manganese-based positive electrode material, the chemical formula of which is Li 1.5 Mn 0.75 Ni 0.75 Co 0.75O3, the specific preparation steps are similar to those of Example 1, except that: (1) lanthanum oxalate is not added, and (2) the obtained solid phase precursor is mixed with lithium hydroxide having a mass of 105% of the total mass of manganese oxalate, nickel oxalate and cobalt oxalate. The remaining steps are the same as those of Example 1.
[0044] Test example
[0045] The lithium-rich manganese-based positive electrode material provided by the present invention is prepared into a positive electrode sheet, and then further prepared into a lithium-ion battery. The specific steps are: the lithium-rich manganese-based positive electrode material prepared in Examples 1 to 3 and Comparative Examples 1 to 3 is respectively mixed with a conductive agent (acetylene black) and a binder (59.323% polytetrafluoroethylene emulsion) in a mass ratio of 16:3:1, anhydrous ethanol is used as a dispersant, ultrasonic dispersion is performed for 10 minutes, and then repeatedly stirred into a mass, rolled into a film, and dried at 130° C. for 30 minutes in an electric heated blast drying oven, and then cut into discs with a diameter of about 1 cm as a positive electrode, a lithium sheet is used as a negative electrode, a Celgard 2400 membrane is used as a diaphragm, and 1 mol / L LiPF6 / EC+DMC+EMC is used as an electrolyte, and assembled into a 2430 type lithium-ion button battery in a glove box filled with argon.
[0046] The electrical performance of the button cell obtained above was tested at a test temperature of 25°C. The test charging method was a constant current constant voltage charging method, and the test voltage range was 2.5~4.75V. The test results are shown in Table 1.
[0047] Table 1
[0048] .
[0049] What is described above is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A lithium-rich manganese-based positive electrode material, characterized in that: The chemical formula is Li 1.5 Mn a Ni b Co c La d O3, where 0.3≤a<0.7, 0.3≤b<0.7, 0.3≤c<0.7, 0.3<d≤0.5 and 1<a+b+c+d≤2; The preparation method of the lithium-rich manganese-based positive electrode material is as follows: adding an appropriate amount of ammonia water into a reaction container, and dropping aqueous solutions of a manganese source, a nickel source, a cobalt source and a lanthanum source respectively, and stirring at the same time to obtain a first dispersion; dropping a lithium hydroxide solution into the first dispersion, and maintaining the pH of the system at 9-11, stirring to react, and performing solid-liquid separation, drying, and grinding to obtain a solid-phase precursor; mixing the solid-phase precursor with lithium hydroxide, and sintering at 700-800° C. under nitrogen protection to obtain the lithium-rich manganese-based positive electrode material; wherein the molar ratios of the manganese source, the nickel source, the cobalt source, the lanthanum source and the lithium hydroxide are 1-4:1-2:1-1.8:1-1.5:1-5, respectively.
2. The lithium-rich manganese-based positive electrode material according to claim 1, characterized in that The chemical formula of the lithium-rich manganese-based positive electrode material is Li 1.5 Mn 0.5 Ni 0.5 Co 0.5 La 0.5 O3.
3. The lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The manganese source is selected from manganese oxalate, manganese acetate or manganese nitrate; the nickel source is selected from nickel oxalate, nickel acetate or nickel nitrate; the cobalt source is selected from cobalt oxalate, cobalt acetate or cobalt nitrate; the lanthanum source is selected from lanthanum oxalate, lanthanum acetate or lanthanum nitrate.
4. The lithium-rich manganese-based positive electrode material according to claim 1, characterized in that The concentrations of the aqueous solutions of the manganese source, nickel source, cobalt source and lanthanum source are all 4-6 mol / L.
5. The lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The concentration of the lithium hydroxide solution is 4-6 mol / L.
6. The lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The concentration of the ammonia water is 1-10 mol / L.
7. The lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The reaction time is 1 to 10 h; the sintering time is 7 to 9 h.
8. A positive electrode sheet, characterized in that: The positive electrode plate comprises the lithium-rich manganese-based positive electrode material according to any one of claims 1 to 7.
9. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet according to claim 8.
Citation Information
Patent Citations
Spherical rich-lithium manganese-base positive electrode material using lanthanum for partially replacing manganese and preparation method thereof
CN106129400A
Carbon nanotube coated H3PO4 modified lithium-rich manganese base positive electrode material and preparation method thereof
CN110783544A